EKSISTENSI METODE BANDONGAN DALAM PEMBELAJARAN TAFSIR PADA PESANTREN DI ERA KONTEMPORER - Afifullah Afifullah (IAIN Madura, 2021)
The views of Van Den Berg and Martin Van Bruinessen was quoted by Rosihon Anwar et.all. stated that the method of learning tafsir used in pesantren in the 19th century was the bandongan and sorogan method. The views of the two figures above are reinforced by Rosihon Anwar et al. in his research conducted in 2015 that the study of tafsir on pesantren in West Java was still dominated by Jala̅layn interpretation by using the bandongan method. Seeing Van den Berg, Martin van Bruinessen and Rosihon Anwar et all.’s reports as if the method that used in Pesantren for tafsir learning just bandongan and sorogan method. Event though globalization, westernization, the modern education system brought by the Dutch, some government regulations that tend to adopt modern education systems in turn always haunt the pesantren. In order to find the background of the existence of the bandongan method in learning interpretation in pesantren in the contemporary era, the author uses a phenomenological approach. The object of the research was carried out at the Islamic boarding school in Sumenep. The results of this study reports that the using of the bandongan and sorogan methods commonly used in pesantren in tafsir learning because it is influenced by several things; first, sufism impact which developed after the collapse of the Abbisayah Dynasty, so it was believed that the kiai were the only source of knowledge or centered teacher as well as murshid in the tarekat. Second, the influence of Zarnuji's book entitled